2021
DOI: 10.3390/ijerph18179021
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Neurological and Psychological Distress Symptoms among Smallholder Farmers in Costa Rica with a History of Acute Pesticide Poisoning

Abstract: Studies suggest that acute pesticide poisonings (APP) may be linked with long-term neurological effects. To examine long-term neurological and psychological distress symptoms associated with having experienced an APP, we conducted a cross-sectional study of 300 conventional and organic smallholder farmers from Zarcero County, Costa Rica, May–August 2016. We collected self-reported data on sociodemographic characteristics, occupational history, pesticide exposure, APPs, neurological and psychological distress s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 37 publications
(50 reference statements)
3
5
0
Order By: Relevance
“…Concerning neurological symptoms, the farmers who applied OP had a significantly higher prevalence of fatigue and paresthesia than those who applied PY (OR = 10.62 and 6.76, respectively). These findings were consistent with the study by Farnham (18) that reported an association between pesticide poisonings and neurological symptoms such as paresthesia or tingling in hands or feet (OR = 3.23), dizziness (OR = 2.38), low energy (OR = 2.33), and tremor of the hands (OR = 3.50) (18). Long-term dermal exposure to OP may cause chronic adverse health effects such as paresthesia and organophosphateinduced delayed polyneuropathy (OPIDP) (56,57).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Concerning neurological symptoms, the farmers who applied OP had a significantly higher prevalence of fatigue and paresthesia than those who applied PY (OR = 10.62 and 6.76, respectively). These findings were consistent with the study by Farnham (18) that reported an association between pesticide poisonings and neurological symptoms such as paresthesia or tingling in hands or feet (OR = 3.23), dizziness (OR = 2.38), low energy (OR = 2.33), and tremor of the hands (OR = 3.50) (18). Long-term dermal exposure to OP may cause chronic adverse health effects such as paresthesia and organophosphateinduced delayed polyneuropathy (OPIDP) (56,57).…”
Section: Discussionsupporting
confidence: 92%
“…In the case of neurobehavioral symptoms, farmers who applied OP had significantly poorer concentration, short term memory, and insomnia than those who applied PY (OR = 13.84, 3.75, and 8.99, respectively). These findings support previous studies that found that organophosphate poisoning in workers had more psychological and affective problems, difficulty concentrating (OR = 2.07), trouble remembering things (OR = 2.54), and insomnia (OR = 2.53) (18,60,61). As a consequence of AChE inhibition, OP exposure causes brain hyperactivity and acetylcholine accumulation (62).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This may be due to the “healthy worker effect” ( 66 ), or to other confounding factors that have not been assessed in this study. Similar findings which also support the present observation were reported from Costa Rica where the loss of appetite, paleness, stomach pain and nausea were more frequently observed in farmers who never experienced health effects than in those who experienced at least one following pesticide application ( 68 ).…”
Section: Discussionsupporting
confidence: 92%
“…In previous studies, several researchers found that environmental exposure to pesticides was associated with a greater prevalence rate and a higher risk of having neurological disorders [ 15 , 16 , 17 ]. However, little is known about the effects of pesticide exposure on sleep.…”
Section: Introductionmentioning
confidence: 99%